Pengaruh Komunikasi Internal terhadap Kinerja Pegawai dengan Partisipasi sebagai Variabel Intervening - Sitti Nurrachmah (Program Studi Hubungan Masyarakat Politeknik LP3I, 2021)
The strategic purpose of communication is related to building a two-way relationship to improve organizational effectiveness, one of the interesting things in effective communication is Internal Communication which has an influence on employee performance. In the behavioral literature, there are a number of aspects of employee attitudes in organizations, including participation and performance. In the context of research, internal communication has an influence on employee performance and participation. The research method used is quantitative, analytical techniques with descriptive statistics that measure the mean, standard deviation, and correlation between variables (zero-order correlation). Statistical testing using path analysis. This study tries to examine the related hypotheses, namely internal communication with participation, internal communication with performance, participation with performance. The results showed that internal communication has a positive influence on participation, internal communication has a positive influence on employee performance, participation has a positive influence on employee performance. The impact of this research is expected that managers can manage internal communication to improve employee performance.